Advantage of ForensiX Swabs in Retrieving and Preserving Biological Fluids1. Issue 3 (15th February 2015) - Mawlood, Shakhawan K.; Alrowaithi, Majid; Watson, Nigel
Abstract This study compares two novel swabs (forensiX) with a standard cotton swab (EUROTUBE) for the collection of saliva stains on glass slide for STR analysis. ForensiX collection tubes are a standard cotton swab in an "active drying" tube, where swab sample is soon dried by its innovative tube surface of the wall. The other is forensiX Nylon Flocked Swab. The study is two phases: The first "phase" assesses swab types regarding to retrieve ability of saliva. The second "phase" compares the drying ability of each swab to assess how crime samples would fare when left in storage. The main result showed that "active drying" is effective to store swabbed sample. The forensiX swabs generally are effective for higher (twofold to fourfold) DNA yield compared to delta lab swab (around 750 pg and 250 pg from 0.5 μL of saliva), respectively. These findings demonstrate the importance of drying performance in the preservation of DNA and swab selection.